8
$\begingroup$

In a group $(Z,*)$, $(a*b)^{5}=a^{5}*b^{5},\forall a,b\in Z$ and $(a*b)^{3}=a^{3}*b^{3}$ then prove that $Z$ is abelian. I know that for three consecutive integer if $(a*b)^{i}=a^{i}*b^{i},\forall a,b\in Z$ holds then $Z$ is abelian. I know i have to use this property and i have to use three consecutive integer $3,4$ and $5$. But i am stuck.

$\endgroup$
3
  • 1
    $\begingroup$ I take it that $Z$ is supposed to be $G$. If so, please edit accordingly. $\endgroup$ Apr 17 '12 at 3:43
  • $\begingroup$ Yes in this case $G=Z$. $\endgroup$
    – Kns
    Apr 17 '12 at 3:45
  • 2
    $\begingroup$ Then edit the question to reflect that! $\endgroup$ Apr 17 '12 at 3:46
25
$\begingroup$

(I'll write $xy$ instead of $x*y$ for simplicity.)

$(ab)^5=a^5b^5\implies ababababab=aaaaabbbbb\implies babababa=aaaabbbb$

$(ab)^3=a^3b^3\implies ababab=aaabbb\implies baba=aabb$

From $baba=aabb$, we get $babababa=aabbaabb$. Combining with $babababa=aaaabbbb$ gives $aabbaabb=aaaabbbb$, so $bbaa=aabb$. Combining again with $baba=aabb$ gives $bbaa=baba$, so $ba=ab$. This is true for any $a,b\in Z$, so $Z$ is abelian.

$\endgroup$
11
$\begingroup$

A group $G$ is said to be $n$-abelian if $(ab)^n = a^nb^n$ for all $a,b\in G$. Given a group $G$, the "exponent semigroup of $G$" is defined to be $$\mathcal{E}(G) = \{n\in\mathbb{Z}\mid (ab)^n =a^nb^n\text{ for all }a,b\in G\}.$$ Properties of $\mathcal{E}(G)$ established by Levi (see this previous answer) imply that if $3,5\in\mathcal{E}(G)$, then $\mathcal{E}(G)=\mathbb{Z}$, giving your desired conclusion.

For a slightly less high-powered proof, note that in general we have that $$(ab)^n = a^nb^n \iff (ba)^{n-1}=a^{n-1}b^{n-1}$$ which can be obtained by cancelling a single $a$ and a single $b$. Therefore, if $n\in\mathcal{E}(G)$, then $$(xy)^{(n-1)^2} = \bigl( (xy)^{n-1}\bigr)^{n-1} = \bigl( y^{n-1}x^{n-1}\bigr)^{n-1} = (x^{n-1})^{n-1}(y^{n-1})^{n-1} = x^{(n-1)^2}y^{(n-1)^2}.$$ That is, $n\in\mathcal{E}(G)$ implies $(n-1)^2\in\mathcal{E}(G)$.

Here, you know $3\in\mathcal{E}(G)$, hence $(3-1)^2 = 4\in\mathcal{E}(G)$. So now we have that $3$, $4$, and $5$ are all in $\mathcal{E}(G)$, and as you note, it is known that if $\mathcal{E}(G)$ contains three consecutive integers then it contains all integers, hence $G$ is abelian.

(This is essentially jgnr's answer, only cast a bit more generally)

As an alternative, but also somewhat high-powered proof, we can follow Steve Ds good observation: by the theorem of Alperin quoted in the answered linked to above, a $3$-abelian group is a quotient of a subgroup of a direct product of abelian groups, groups of exponent $3$, and groups of exponent $2$; but the latter are abelian as well, so $G$ will be a quotient of a subgroup of a direct product of abelian groups and groups of exponent $3$. If you had an element that is not central (that does not commute with everything) then it would have to be an element of order $3$. But by the same characterization, since $G$ is $5$-abelian it is a quotient of a subgroup of a direct product of abelian groups, groups of exponent $4$, and groups of exponent $5$. So a noncentral element would have to have order dividing $20$. Since $\gcd(3,20)=1$, there can be no noncentral elements (it would have to have exponent $3$ and exponent $20=4\times 5$, hence exponent $1$, hence be trivial, hence it is central). So $G=Z(G)$, hence $G$ is abelian.

$\endgroup$
2
  • 2
    $\begingroup$ Surely Alperin's result is good enough here? 3-abelian implies the only non-central elements must have exponent 3, which are ruled out by 5-abelian. $\endgroup$
    – user641
    Apr 17 '12 at 4:23
  • $\begingroup$ @SteveD: Good point; yes. $\endgroup$ Apr 17 '12 at 4:29
0
$\begingroup$

Here, consider $(G,\circ) \equiv (Z,*)$ Let, $a, b \in G$. Now, using $a^3 \circ b^3 =(a \circ b)^3$ and $a^5 \circ b^5 =(a \circ b)^5$ :

$(a^3 \circ b^3) \circ (a\circ b)^2 =a^5 \circ b^5$ $ \implies a^3 \circ b^3 \circ (a \circ b)^2 = a^2 \circ (a \circ b)^3 \circ b^2 $ $\implies a \circ b^3 \circ (a \circ b)^2 = (a \circ b)^3 \circ b^2 \implies (a\circ b) \circ b^2 \circ (a \circ b)^2 = (a \circ b)^3 \circ b^2 \implies b^2 \circ (a \circ b)^2 = (a \circ b)^2 \circ b^2$

As $a \circ b= c \in G \forall a, b \in G$, therefore: $b^2 \circ c^2 = c^2 \circ b^2 \implies c \circ b^2 \circ c^2 \circ b= c^3 \circ b^3 \implies (c\circ b)\circ ( b\circ c) \circ (c\circ b) = (c\circ b)^3 \implies b\circ c = c\circ b$, i.e the Group is abelian

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.